Molecular structure, characterization, in vitro and in-silico studies of N,N-dimethyl aminophenyl schiff's base-chalcone hybrid - Rajendran Nithyabalaji; Rajan M.P. Ramya; Rengarajan Kavitha; Kothalam Radhakrishnan; Jothi Vinoth Kumar; Bandar Ali Al-Asbahi; Merum Dhananjaya; Sang Woo Joo (Chemical Physics Impact, 2024)
This study reports the synthesis and characterization of a novel compound, a chalcone-based Schiff base (SBC), with potential applications in anti-inflammatory and anti-diabetic treatments. Chalcones, known for their diverse biological activities, are combined with Schiff bases, versatile compounds, to create the SBC. The synthesis process involves aldol condensation and Schiff base formation. The compound's structure is confirmed through NMR, FT-IR, and mass spectroscopic analyses. The UV–visible spectroscopy reveals the compound's electronic properties, and molecular docking experiments indicate its potential to interact with enzymes related to inflammation and diabetes. Anti-inflammatory activity is evaluated through a protein denaturation assay using bovine serum albumin. SBC demonstrates significant anti-inflammatory activity, outperforming standard drug molecules, and exhibits concentration-dependent effects. In an α-amylase inhibitory assay, a vital enzyme in the digestive process related to diabetes, SBC shows remarkable inhibition, surpassing standard drug performance, especially at higher concentrations. Molecular docking studies suggest the compound's potential interactions with enzymes responsible for inflammation and diabetes. SBC displays strong binding energies and inhibition constants with α-amylase, indicating its suitability for diabetes-related studies. The synthesis and characterization of SBC, combined with its excellent anti-inflammatory and anti-diabetic activities, underscore its potential as a promising candidate for further biomedical research and therapeutic development.